STATUS OF SPATIAL ASYMMETRY OF CUSTOMS SPACE IN UKRAINE - Сидор, Галина Вікторівна; Андрусів, Уляна; Вербіцька, Інеса (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
Purpose. Identify and evaluate the spatial asymmetry of Ukraine customs space in the context of identifying opportunities and prospects for balancing it and enhancing its effectiveness. Methodology of research. Theoretical and methodological basis of the research is the scientific works of domestic and foreign authors on the study of the spatial asymmetry of the customs space of Ukraine, Internet resources. In the course of the research, general and special methods were used, in particular: economic-statistical and calculation-analytical methods for carrying out a complex analysis of the monitoring of the spatial asymmetry of the customs space in Ukraine; abstract-logical and dialectical methods of analysis to substantiate theoretical propositions and conclusions. The techniques of graphical display of results are applied in the article. Findings. The state of spatial asymmetry of the customs space in Ukraine is analyzed, using indicators(number of enterprises that imported goods, volume of imports of goods, number of enterprises that exported goods), that characterize the customs and foreign trade component, as well as the economic development of the country. The spatial asymmetries of the customs space of Ukraine in the context of determining the prospects and opportunities to increase its efficiency and balance are assessed. An appropriate customs environment has been developed to continue and support the development of trade relations with other countries. Originality. The state of spatial asymmetry of the customs space of Ukraine in the context of determining the possibilities and prospects of its balancing and improving the efficiency is considered. Practical value. The results of the study reflect the current state of spatial asymmetry of the customs space in Ukraine and are the basis for overcoming the negative aspects and obstacles to its functioning.